Understanding the Delivery of Patient-Centered Survivorship Care Planning: An Exploratory Interview Study With Complex Cancer Survivors. (22nd October 2021) - Austin, Jessica D.; Allicock, Marlyn; Fernandez, Maria E.; Balasubramanian, Bijal A.; Lee, Simon Craddock
Introduction: Understanding key elements of the survivorship care planning process, such as patient-centered communication (PCC) and health self-efficacy, are critical for delivering patient-centered survivorship care to cancer survivors with multiple chronic conditions ("complex cancer survivors"). Building upon our team's recent research efforts to examine the survivorship care planning process from a patient-centered lens, this exploratory study leveraged an ongoing quasi-experimental trial to elucidate the experience of complex cancer survivors with survivorship care planning and post-treatment management. Methods: We conducted a hypothesis-generating thematic content analysis on 8 interview transcripts. Results: Survivors reported positive experiences communicating with their oncology care team but the presence of multiple chronic conditions in addition to cancer creates additional barriers to patient-centered survivorship care. Conclusion: These findings support the need for further in-depth research aimed at improving PCC across all care teams and enabling self-management by delivering more personalized survivorship care planning that aligns with survivor's needs, values, and preferences.